Application of Coconut Shells Charcoal and Cow Feces (Bokashi) on the Growth of Jabon Seedling at the Gold Mine Tailings Medium - Basuki Wasis; Ari Istantini (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Mining is one potential natural resources that can be used as a source of foreign exchange to national development. Activities in mining inflict negative impact on the environment in form of the damaged environment, habitat animals and loss of the kinds of flora/fauna endemic. To prevent and reduce the destructive power worse, we need to sought various effort control that lead to activity land rehabilitation one is modifying environment growing crops. One of them is giving coconut shells and bokashi on jabon to increase plant growth and productivity on critical land after mine for a relatively cheap.This research used data measurement of primary growth of jabon in the press cropping former gold mine (tailing). The method is applicable in the measurement of on high growth, diameter, the total weight of dry and NPA jabon on tailing with treatment granting coconut shells charcoaland bokashi in various doses for three months. Diverse analysis with the (Pr>f)<α (significant value<0.05)or influence the provision of charcoal and bokashi influential real on the growth of high In diameter, the total weight of dry and NPA of jabon on tailing, then test the continued to compare the middle value treatment. Further test used Duncan test.Based on the results, it can be said the addition of charcoal and bokashi were able to repair the structure and texture of the medium, so it can improve the tailings deposits of nutrient elements for plants. Treatment A4B3 (granting of charcoal with a dose of 10% and bokashi with a dose of 60 g) delivers the most flattering to increased growth of jabon on the gold mine tailings medium.Key words: Anthocephalus cadamba, bokashi, charcoal, growth, tailing